Elevated Circulating IL-10 Producing Breg, but Not Regulatory B Cell Levels, Restrain Antibody-Mediated Rejection After Kidney Transplantation - Luo, Yongsheng; Luo, Feifei; Zhang, Kuanxin; Wang, Shilei; Zhang, Haojie; Yang, Xianlei; Shang, Wenjun; Wang, Junxiang; Wang, Zhigang; Pang, Xinlu; Feng, Yonghua; Liu, Lei; et al. (Frontiers in Immunology, 2021)
Background: Antibody-mediated rejection (AMR) occupies a major position for chronic rejection after kidney transplantation. Regulatory B cell (Breg) has been reported to have an inhibitory immune function, which contributes to the resistance for AMR. Methods: A nested case-control study for nine healthy donors, 25 stable (ST) patients, and 18 AMR patients were performed to determine the type of Breg in maintaining immune tolerance and preventing AMR. Results: Compared to the ST group, circulating interleukin (IL)-10+ Bregs, but not Bregs, significantly decreased. The receiver operating characteristic (ROC) curve analysis revealed that rather than the circulating Bregs, decreased circulating IL-10+ Breg levels were positively associated with AMR. However, kidney B cell and IL-10 infiltration were significantly increased in the AMR group with high expression of C-X-C motif chemokine 13 (CXCL13). In addition, circulating IL-10+ Bregs, rather than Bregs, remained higher than those at pre-operation, during the 90-day post-operation in immune homeostasis. Conclusion: The circulating IL-10+ Breg levels are more appropriate measures for assessing the resistance of AMR after kidney transplantation.